A&T Ethiopia Complementary Feeding Baseline Survey 2015: Households - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household survey that was conducted to gather data at baseline as part of the study assessing the impact of the A&T social and behavior change communication (SBCC) interventions in the Amhara region of Ethiopia. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. A&T's focus in this phase of the study in Ethiopia (with program implementation from late 2014 to 2017) is on operationalizing the IYCF component of the Government of Ethiopia’s National Nutrition Plan (NNP) in one region, Amhara. The objectives of the A&T initiative in Amhara are as follows: 1) Sustain high rates of EBF among children 0–5.9 months at over 70 percent in A&T program areas, 2) Increase the proportion of children 6–23.9 months of age who receive a diverse diet (at least four food groups) by 10 percentage points in A&T program area, and 3) Increase the proportion of breastfed and non-breastfed children 6–23.9 months of age who receive solid, semi-solid, or soft foods at least the minimum number of times per day by 10 percentage points in A&T program areas. A cluster-randomized design with repeated cross-sectional surveys at baseline (2015) and endline (2017) were used to assess impact of the A&T social and behavior change communication (SBCC) interventions in Amhara region, particularly the community-based interventions (interpersonal communication and social mobilization) and mass media activities. The evaluation includes household and frontline worker (FLW) surveys. Twenty woredas (districts) were purposively selected as potential areas of work by A&T HQ and Save the Children, and the select woredas were randomly assigned as 10 intervention (or A&T-intensive, A&T-I) and 10 comparison (or A&T-Non intensive, A&T-NI) woredas. The baseline survey applied four structured questionnaires: (1) household questionnaire and anthropometric measurements of children and mothers, (2) community questionnaire, (3) frontline worker questionnaire: Health extension worker (HEW), and (4) Frontline worker questionnaire: Health development army team leader (HDTL). A household roster was used to gather information on household composition and characteristics of each member (age, gender, and education). The household questionnaire captured exposure to key program elements as well as standard services. Intermediate factors of knowledge, awareness, trial, and adoption of recommended practices and underlying factors related to the child, mother, and household were also collected. Questionnaires were administered to mothers of the child selected for the survey. Anthropometric measurements (height and weight) were also collected for both mother and child in each household.